2013
DOI: 10.4102/td.v9i1.220
|View full text |Cite
|
Sign up to set email alerts
|

Establishing and maintaining international collaborative research teams: an autobiographical insight

Abstract: Despite the growing impetus for international collaborative research teams (ICRT), there are relatively few resources available to guide and support researchers through the processes of establishing and maintaining ICRTs. In particular, no articles were found that provided researchers' firsthand accounts of being a member of such a team. Having access to such personal accounts can help both experienced and novice researchers learn more directly about what to expect, as well as the benefits, challenges, pitfall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The findings from this study highlight that collaborative research teams provide an opportunity for likeminded academics, irrespective of research experience, to share knowledge and develop research profiles in a proficient yet enjoyable manner. Most notably these participants identified that collegiality, authenticity and working alongside researchers with shared aspirations and goals were important aspects of the collaborative process and, as such, align with previous studies by Carr et al (2013), Bozeman and Boardman (2014) and Yuan and Jing (2014). Furthermore, participants' personal values such as trust and respect were key to the team becoming a cohesive unit through which creativity flourished.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The findings from this study highlight that collaborative research teams provide an opportunity for likeminded academics, irrespective of research experience, to share knowledge and develop research profiles in a proficient yet enjoyable manner. Most notably these participants identified that collegiality, authenticity and working alongside researchers with shared aspirations and goals were important aspects of the collaborative process and, as such, align with previous studies by Carr et al (2013), Bozeman and Boardman (2014) and Yuan and Jing (2014). Furthermore, participants' personal values such as trust and respect were key to the team becoming a cohesive unit through which creativity flourished.…”
Section: Discussionsupporting
confidence: 78%
“…A collaborative research team can be defined as a coalition between researchers who share collective goals, aspirations and responsibilities in conducting research (Carr et al, 2013). Collaboration between institutions and across international borders brings research talent together to work on complex projects that would be difficult to conduct in isolation (Broome, 1999; Carr et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations